Extracting Induced and Remanent Magnetizations From Magnetic Data Modeling. Issue 11 (9th November 2018) - Liu, Shuang; Fedi, Maurizio; Hu, Xiangyun; Baniamerian, Jamaledin; Wei, Bangshun; Zhang, Dalian; Zhu, Rixiang
Abstract: To investigate the crustal magnetic structure, it is important to assess the susceptibility and remanence properties of rocks and ores. In this paper, we propose a method to extract the contributions of induced and remanent magnetization from modeling of magnetic anomalies. We first estimate the direction of the total magnetization vector by studying the reduced‐to‐pole anomaly and its correlation with different magnitude magnetic transforms. Then we invert the magnetic data to obtain the volumetric distribution of the magnetization intensity. As the third step, based on a priori information about the Koenigsberger ratio derived from petrophysical measurements, we extract the distributions in the source volume of the induced and remanent magnetization intensities, based on a generalized relationship involving the total and remanent magnetizations, and the true susceptibility. In this way, we are able to produce separate maps of the anomaly fields attributed to the physical magnetic source parameters: remanent and induced magnetization. After validating the method with synthetic data, we analyze the data relative to the Mesozoic and Cenozoic igneous rocks in Yeshan region, eastern China. The analysis of the separated magnetization components reveals that the intrusion of dioritic and basaltic rocks occurred at different geological periods, and the basaltic rocks were magnetized by a reversed geomagnetic field. The uncertainty analysis shows that a larger Koenigsberger ratio is beneficial to extract more reliable remanence and susceptibility information. Key Points: An inversion method of magnetic data in the presence of remanent magnetization is proposed Induced and remanent magnetizations are estimated for each block of the source domain, and corresponding magnetic anomalies are extracted Yeshan region (eastern China) is studied, where Cenozoic basalts were formed during a period of reversed direction of the geomagnetic field